Industrial wastewater treatment using advanced chemical oxidation with fenton reagent - Rodrigues, CD (2009)
Advanced oxidation with Fenton's reagent is a promising technology for removal of toxic and non biodegradable organic compounds present in wastewaters produced in semiconductor and wood production industries. The objective of this work was to optimize COD removal from the industrial wastewaters, by applying advanced oxidation processes with Fenton's reagent. In this study, the effect of three variables (reaction time, initial hydrogen peroxide and ferrous ion concentration) on COD removal from two different industrial wastewaters was evaluated. For this purpose, an experimental design with two levels and three variables was used leading to the conclusion that reaction time is the only variable that has a statistical meaning for semiconductor industry wastewater treatment. The best %COD removal that could be attained for Fenton oxidation of this wastewater (with an initial COD of 21-32 g O2/L) was 75%, when reaction started at pH = 3, adding hydrogen peroxide at 4.2M concentration and ferrous ions at a FeSO4: H2O2 mass ratio of 1:5 for a 4h reaction time. When optimizing the treatment of wastewater from wood production (with an initial COD of 25 g O2/L) with Fenton's reagent, also an experimental design with two levels and three variables (reaction time, initial hydrogen peroxide and ferrous ion concentration) was used. For this wastewater, all of the three variables have shown statistical meaning, as well as the interaction between each other. The conditions that conducted to the best results (%COD removal = 82%) were: initial pH = 3, [FeSO4] = 50 mM, [H2O2] = 4.2 M and reaction time = 60 min.